Reflection as transformative praxis : an exploration of early-career ecturers’ pedagogical reflections in academic induction - Sithole, Mashango Phillemon; Chia, Evelyne; Chabaya, Owence; Wadesango, Newman (African Perspectives of Research in Teaching & Learning (APORTAL), 2025)
This study investigates how early-career lecturers in a South African university reflect on their teaching philosophies and practices during academic induction, and how such reflection shapes their professional identities within contexts of institutional constraint. Drawing on Schön’s Reflective Practice Theory, Mezirow’s Transformative Learning Theory, and Barnett’s notion of critical being, the study conceptualises reflection as transformative praxis. Herein, it is a recursive process that fuses cognition, emotion, and ethics. Using interpretive thematic analysis of thirty-eight induction reflective homework submissions, the findings reveal reflection as both a pedagogical and moral act that enables lecturers to adapt, humanise, and reimagine teaching amid systemic inequalities. Reflection functions as an instrument of agency, resilience, and epistemic justice, bridging personal transformation with curriculum renewal. The study contributes to scholarship on academic induction by reframing reflection as a moral and relational project that underpins professional becoming and decolonial transformation in African higher education.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 7, Volume 9, 2025 Special Issue
Keywords: Academic induction; Early-career lecturers; Professional identity; Higher education; Reflective practice; Transformative learning; Employee orientation; Employees -- Training of; Education higher, South Africa; Transformative learning; Teaching -- Evaluation; Reflective teaching